The benefit-risk analysis of omega-3 polyunsaturated fatty acids and heavy metals in seven smoked fish species from Siberia - Michail I. Gladyshev; Olesia V. Anishchenko; Olesia N. Makhutova; Olesia V. Kolmakova; Maria Y. Trusova; Vasiliy N. Morgun; Iliada V. Gribovskaya; Nadezhda N. Sushchik (Journal of Food Composition and Analysis, 2020)
In cold-smoked species of genus Coregonus, identified by molecular genetic analysis, contents of fatty acids and heavy metals and arsenic were measured. The highest content of sum of long-chain polyunsaturated fatty acids of omega-3 family (LC-PUFA), namely eicosapentaenoic (EPA) and docosahexaenoic (DHA) fatty acids, 6.53 ± 0.78 mg g−1 wet weight, was characteristic of tugun Coregonus tugun. This is the first quantitative estimation (mg LC-PUFA per g of product) of the nutritive value of smoked fish. Thus, to obtain a daily personal doze of EPA+DHA of 1 g, recommended for prevention of cardiovascular diseases, one needs to consume 153 g of the smoked tugun. Metals' contents did not exceed standards for fish meat except Pb in least cisco Coregonus sardinella. Accordingly, values of hazard quotients, which estimate benefit-risk ratio of fish intake, indicate that most of the smoked fish species are safe product for human nutrition, except least cisco regarding Pb content.